Oxygen uptake kinetics during heavy submaximal exercise: Effect of Sickle Cell Trait with or without Alpha-Thalassemia - Connes, P.; Monchanin, G.; Perrey, S.; Wouassi, D.; Atchou, G.; Forsuh, A.; Debaud, J.; Djoda, B.; Owona, F. X.; Francina, A.; Banga, P. E.; Massarelli, R.; et al. (International Journal of Sports Medicine, 2006)
Sickle cell trait (SCT) is a genetic disease affecting the synthesis of normal hemoglobin (Hb) marked by the heterozygous presence of HbA and HbS. It is thought that exercise tolerance and aerobic capacity could be limited in SCT carriers, but that the co-existence of alpha-thalassemia with SCT (SCTAT) could improve exercise response. To examine these issues, we compared the characteristics of V·O2 kinetics during a constant heavy exercise among athletes carrying either the SCT (n = 6), the SCTAT (n = 9), or the normal Hb (control group; n = 10). After determination of maximal power output (Ppeak), all subjects underwent a constant heavy cycling exercise lasting 9 min at ~ 70 % Ppeak. Pulmonary V·O2 and cardio-respiratory parameters were measured breath-by-breath and the V·O2 response was modelled using non-linear regression techniques. The time constant of the V·O2 primary component and oxygen deficit were not significantly different among the three groups. The V·O2 slow component was 28 % and 33 % higher (p < 0.05) in SCT and SCTAT than in the control groups, respectively. Altogether, athletes with the SCT and the SCTAT had higher heart rate at the beginning (+ 5.2 %) and the end (+ 7.4 %) of the slow component compared to the control group (p < 0.05). These results suggest that SCT and SCTAT subjects are not limited during the first exercise minutes, but are prone to exercise intolerance and to lower aerobic capacity thereafter, due to a higher V·O2 slow component, and that a-thalassemia does not improve exercise response. The finding of a higher slow component in SCT and SCTAT athletes was possibly due to the loss of O2 availability to muscles, additional fiber recruitment and/or higher cardiac load with time.